Investigating the Post-Mortem Interval (PMI) with Forensically Important Necrobiomes (Indian Journal of Forensic Medicine & Toxicology, 2023)
Estimating the post-mortem time interval (PMI) is a crucial component of the forensic investigation and is extremelydifficult for medico-legal experts to do. After death, the succession of microbes in various parts of the human bodyhas enormous potential for predicting PMI. The human body is home to trillions of commensal microorganisms.These microbes behave in a different way when biological processes stop, which coincides with the death of anindividual and the invasion of deteriorating microbes from the environment. Due to cell autolysis, which draws avariety of invasive macro- and microorganisms, human cadavers become a rich source of nutrients. The successionof microorganisms differs significantly at various stages of degradation, which can be investigated for precisePMI estimation. Necrobiome analysis has drawn a lot of attention in PMI estimation due to the developmentof microbial genomics technology and decrease in the price of DNA sequencing. The review article provides asummary of the various microorganism sources, their successional pattern, and analytical methods that can beused in the field of microbial forensics.
Keywords: Necrobiome, Microbial diversity, Decomposition analysis, Post-Mortem Interval (PMI), Time Since Death (TSD), Microbial Forensics.